Purposes and mechanisms of goal planning in rehabilitation - Playford, Diane (Rehabilitacija (Ljubljana), 2018)
Goal setting has been defined as a process of discussion and negotiation in which the patient and staff determine the key priorities for that individual and agree the performance level to be attained by the patient for defined activities within a specified time frame. It is regarded as a core skill of rehabilitation professionals (1), but the evidence that it makes a difference to patients is limited. A recent Cochrane review of goal setting in rehabilitation practice suggested that there was some very low quality evidence that goal setting may improve some outcomes but this was mainly around attributes such as self efficacy rather than physical function (2). Goal setting takes considerable time and effort (3) which raises the question is it worth while? The purposes of goal setting vary in different patient groups, and in different settings. Experienced clinicians focus on the process of discussion and negotiation, whereas younger clinicians focus on the articulating the goal in a way that can be seen as SMART (4). This would suggest that these are two different activities. SMART goal setting has captured the imagination, but there are some difficulties with it. Few people set themselves SMART goals, and when they do, such as at New Year, they often break them. People use SMART goals in the work-place, and these can be helpful when the goals are specific, jointly set and reasonable, the manager is regarded as helpful, facilitating, receptive to ideas and able to plan and evaluation of performance is initiated by subordinates and as a prelude to further goal setting, not appraisal. The difference between work and rehabilitation is that everyone should be clear about the "mission" of their workplace, and the goals are designed to make the workplace more efficient. What, then, is the mission of rehabilitation? Is it to manage impairment, increase activity and participation, prepare patients for discharge from hospital, or something else? Before rehabilitation professional set goals, we need to be clear about why we are doing so, as this will affect how we set goals and our approach to doing so.
Keywords: dolgoročni cilji; določanje ciljev; Goals; goals setting; long temn outcomes; mechanisms; mehanizmi; rehabilitacija; Rehabilitation; vocational rehabilitation